2001
DOI: 10.1111/1468-0297.00665
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and Subsequent Earnings: Estimating Scarring Among British Men 1984–94

Abstract: This paper estimates the impact of unemployment on earnings following re-employment for a large and representative sample of British men, 1984±94. Unemployment incidence is found to have only a temporary effect, an average earnings setback of 10% on initial re-engagement largely eroding over two years. The effect of unemployment duration, by contrast, is permanent, a one-year spell adding a further penalty of 10 percentage points. These wage penalties are least for young men and the low paid ± those most at ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
110
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(130 citation statements)
references
References 20 publications
16
110
2
2
Order By: Relevance
“…For men, unemployment could also be a crucial factor for timing of parenthood. The economic consequences of unemployment are obvious: loss of current income, potential loss in future wages (Arulampalam 2001), and risk of subsequent unemployment spells (Arulampalam 2002;Arulampalam et al 2001;Gregory and Jukes 2001). Also widely documented in the literature is the fact that unemployment has an immense deteriorating impact on men"s physical and psychological well-being (see for example Clark 2003;Clark et al 2001;Clark and Oswald 1994;Frey and Stutzer 2002;McKee-Ryan et al 2005;Murphy and Athanasau 1999;Nordenmark 1999, Nordenmark andStrandh, 1999;Whelan et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…For men, unemployment could also be a crucial factor for timing of parenthood. The economic consequences of unemployment are obvious: loss of current income, potential loss in future wages (Arulampalam 2001), and risk of subsequent unemployment spells (Arulampalam 2002;Arulampalam et al 2001;Gregory and Jukes 2001). Also widely documented in the literature is the fact that unemployment has an immense deteriorating impact on men"s physical and psychological well-being (see for example Clark 2003;Clark et al 2001;Clark and Oswald 1994;Frey and Stutzer 2002;McKee-Ryan et al 2005;Murphy and Athanasau 1999;Nordenmark 1999, Nordenmark andStrandh, 1999;Whelan et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…We compute this variable by generating the average curricular number of years for the highest degree attained by 2005 21 . Table 1 reports descriptive statistics of our dependent and explanatory variables.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…20 Potential experience is usually measured as: age -years of schooling -5. 21 We set years of schooling to 14 years for those with a trade/vocational diploma or college/CEGEP certificate, 15 years for university diploma or certificate below bachelor's level, 17 years for a bachelor's degree, 18 years for a university diploma or certificate above bachelor's level but below master's level, 19 years for a master's degree, and 22 years for respondents with an earned doctorate. However, some suggested that education levels should replace schooling years in the wage equation.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Furthermore, scarring of the wage level was not found to occur for workers who experience a break in employment whilst young, but had an increasing effect for those who experienced unemployment during what would otherwise be prime years of employment. Gregory and Jukes (2001) found a spell of unemployment to reduce wages by 10% with this penalty diminishing over time, but that a long spell of unemployment had a lasting outcome that increased for those of prime age and with higher pay.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large literature examining scarring (e.g. Arulampalam, Gregg, & Gregory, 2001;Gregory & Jukes, 2001;Knabe & RÄTzel, 2011), much of it concerned with the effect of a period of unemployment on subsequent wage level or employment (Nilsen & Reiso, 2011), there has been little engagement, within this literature, with the concept of NEET per se. Knabe and RÄTzel (2011) examine the psychology of scarring and show a negative psychological scar related to past unemployment that manifests itself in a fear of future unemployment.…”
Section: Introductionmentioning
confidence: 99%